PENGGUNAAN LITERASI DIGITAL DALAM MEMBANGUN MINAT BACA PADA SISWA FASE KELAS B - Farida Putri Fauziansyah; Ema Mutiara Hasanah; Fitriyatul Romadiani; Musfiroh Musfiroh; Muhammad Romli (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Digital literacy is an important skill in the increasingly digitalized information era. In today's digital era, children are very familiar with technology so that a digital-based learning approach is one of the effective strategies for fostering reading habits. This study aims to describe how the use of digital media such as interactive e-books, learning videos, and online reading platforms can increase students' enthusiasm and motivation in reading. The results of the study show that digital literacy not only enriches reading sources but also encourages active student involvement through content that is more interesting and in accordance with their learning styles. With the right integration of digital literacy, teachers can create a learning environment that is more inclusive, enjoyable, and in accordance with students' developmental needs. Therefore, it is important for educators to continue to improve digital competence in supporting adaptive and sustainable learning processes.